Injury Characteristics and Forensic Medical Outcomes in Non-Fatal Work Accidents - Emre Gürkan Bulutluöz; Burak Kaya (Turkish Journal of Forensic Medicine, 2026)
Aim: This study aimed to evaluate the epidemiological, clinical, and forensic medical characteristics of injuries resulting from non-fatal occupational accidents and to determine their medico-legal qualifications within the framework of the Turkish Penal Code (TPC).Methods: Cases presenting to Çankırı State Hospital between 1 January 2022 and 31 December 2025 and assessed as forensic cases were retrospectively reviewed, and 917 cases with documented occupational accidents were included in the study. The data were analyzed in terms of demographic characteristics, sector, time and location of the accident, mechanism of injury, injured body regions, and forensic medical evaluation criteria.Results: Of the cases, 79% were male, with a mean age of 32.5±11.2 years. Occupational accidents most frequently occurred in the industrial/manufacturing (48.1%) and construction (11.1%) sectors, predominantly on weekdays and during working hours. The majority of injuries were due to blunt trauma (65.1%), with compression/crushing/fall identified as the most common mechanism (43.7%). The upper extremity was the most frequently affected body region (53.8%), with fractures observed in 18.6% and amputations in 4.4% of cases. In the forensic medical evaluation, 71.6% of injuries were classified as treatable with simple medical intervention and 2.2% were determined to be life-threatening.Conclusion: Occupational accidents appear to be concentrated in high-risk sectors, and a substantial proportion results in significant medico-legal consequences; these findings indicate the need to develop preventive strategies and to strengthen and standardize forensic reporting processes.